Artery of percheron occlusion: a rare cause of coma. Issue 5 (8th May 2017) - El-Wahsh, Shadi; Weerasinghe, Dinushi; McDougall, Alan
Abstract : Objectives: To present a case of artery of Percheron (AOP) occlusion and discuss the neuroimaging and clinical differential diagnosis. Case: A 40-year-old male with no past medical history was found unconscious by his work colleagues. On presentation, he had a GCS of 7 (E3, V1, M3) and a left dilated unreactive pupil. He had no witnessed seizure activity and displayed no focal neurological deficits. Immediate brain imaging showed no evidence of intracranial haemorrhage or basilar artery occlusion. He was intubated and treated empirically for seizures and encephalitis. Lumbar puncture was negative and an EEG performed 24 hours later revealed no seizure activity. An MRI done 72 hours after the event revealed bi-thalamic infarction, suggestive of AOP occlusion. He was extubated 4 days after presentation. He displayed intermittent drowsiness throughout the day, as well as a vertical gaze palsy. Mobility was significantly impaired secondary to reduced dynamic balance but he had no sensory or motor deficits and no cerebellar signs. MRI scans revealed an associated small left cerebellar hemisphere infarct, suggesting an embolic aetiology. The patient underwent a full young stroke work-up, including vasculitic and thrombophilia screen, which were unremarkable. Transoesophageal echocardiography identified no cardiac source of embolus and no patent foramen ovale. The decision was made to commence anti-coagulation with apixaban. Three-weeks post onset, the patient had an ongoing vertical gaze palsy but improved levels of alertness, and is awaiting in-patient rehabilitation to improve mobility. Conclusions: AOP occlusion is a rare cause of coma and should be suspected in patients who present with acute loss of consciousness, once other common aetiologies are excluded. This case raises pertinent questions regarding the indications and benefits of thrombolysis and/or clot retrieval in such patients.